Dilema Perizinan Alih Fungsi Bangunan Rumah Dinas TNI di Era Otonomi Daerah - Purwanto, Adinda Putri; Pahlevy, Rifqi Ridlo (ResearchJet Journal of Analysis and Inventions, 2024)
This study aims to apply the TNI Commander Regulation No. 49 of 2015 concerning the Utilization of State Property in the form of Land and/or Buildings within the TNI at the Home of the Military Command V Brawijaya Waru. The research method used is Socio Legal using a juridical approach and a sociological approach. The results of the study were seen from the practice at the Kodam V Brawijaya Waru official house, which is one of the buildings under the auspices of the competent agency within the TNI. Building a building is one of the activities to construct, update and expand houses or buildings converted into a place that allows it to be used for everything. From this research, it can be concluded that changing the function of this official house building must be adjusted to the permit of the TNI Commander Regulation No. 49 of 2015 and its law enforcement based on the competent authority in warning letters and fines that will be carried out, the existence of this TNI Commander Regulation is very important because it uses the Lex Specialis Derogate Generalis Principle.